Deeper, broader, longer transitional justice. (July 2014) - Nickson, Ray; Braithwaite, John
Transitional justice has an expectation management problem. International law imposes a right to justice and an obligation to defeat impunity from crimes against humanity. Yet there has not been a war where a substantial proportion of criminals against humanity have been convicted. Nor is one likely. The theoretical solution considered in this paper is to broaden, deepen, and lengthen our conception of justice so that more survivors might be vindicated by some kind of justice, even if a partial kind of justice. We broaden justice with a more holistic, yet multidimensional conception of what justice means, so that, for example, restorative justice, Islamic justice and indigenous justice can be embraced among many alternatives to impunity. Deepening justice means deeper survivor and citizen opportunities to shape a more responsive justice and to shape remedies through participation. Lengthening justice means giving less priority to speedy trial and closure as transitional justice values. It might mean a permanent Truth and Reconciliation Commission that keeps its doors open to victims decades on.